Determining Consumer Intentions Towards Using Sharia Fintech Lending: Technology Acceptance Model Approach - Lifatin Nada; Azzatillah; Rinda Dwi Pradina; Ilham Teguh Setiawan; Feri Zain (Mabsya: Jurnal Manajemen Bisnis Syariah, 2025)
Conventional and Islamic fintech lending in Indonesia has experienced relatively rapid development. However, the accumulation of financing distribution of Islamic fintech lending is still far below that of conventional fintech lending. Demographic factors, namely the majority of the Indonesian Muslim population, do not make Islamic fintech lending their primary choice for borrowing funds online. Based on the Technology Acceptance Model theory, this study analyses the factors influencing consumer intentions to borrow from Islamic fintech lending. The analysis of this study uses a variant-based Structural Equation Model (SEM) with Partial Least Squares (PLS). The sampling technique uses purposive sampling and obtains 113 data points. The study's results indicate that subjective norms positively affect perceived usefulness and ease of use, and perceived ease of use positively impacts the perception of usefulness. The subjective norms and perceived usefulness have been proven to be significantly positive in encouraging the intention to borrow in Islamic FinTech lending. In contrast, the perceived ease of use has not been proven to influence the intention to borrow in Islamic Fintech lending. The moderating variable in this study, namely knowledge of usury, is proven unable to moderate the relationship between subjective norms, perceived usefulness, and perceived ease of use on the intention to borrow in Islamic fintech lending.